The Urn and the Swastika: Recording Death in the Nazi Camp System. Issue 1 (19th December 2019) - Lambertz, Jan
Abstract: Why did Nazi concentration camps routinely send death notifications and even cremation urns to families of dead prisoners, including Jewish prisoners, until well into the war years? This article challenges the assumption that these practices served solely to provide reassurance that the prisoners had died under 'normal' circumstances. In the case of Jewish prisoners, urns sent home for burial to families in the Reich were part and parcel of a system of intimidation waged through local Gestapo offices. These urns also illuminate changing practices around prisoner deaths within camps themselves and the dissonant character of Nazi camp organization. On the one hand, camp administrators adhered to long-standing German state practices, establishing civil registries on camp premises to record prisoner deaths. On the other hand, they flouted bureaucratic norms, fabricating the causes of prisoner death on a grand scale and using bureaucratic procedures to veil the gross mistreatment of inmates. In many camps, prisoner labour was forced to help manufacture and uphold this imperfect subterfuge. These histories point to one of the few places in which the death of Jewish prisoners in the Nazi detention system was systematically recorded and conveyed back to families and Jewish communities in the Reich. Yet, paradoxically, the 'processing' of death in the major concentration camps was in many respects untrustworthy, and intimidation now also hovered over what had been a credible, neutral civil procedure.